2015
DOI: 10.1016/j.jbiomech.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel alters sensory nerve biomechanical properties

Abstract: Paclitaxel is an effective chemotherapeutic that, despite its common use, frequently causes debilitating peripheral sensory neuropathy. Paclitaxel binds to and stabilizes microtubules, and through unknown mechanisms, causes abnormal microtubule aggregation. Given that microtubules contribute to the mechanical properties of cells, we tested the hypothesis that paclitaxel treatment would alter the stiffness of sensory nerves. Rat sural nerves were excised and soaked in Ringer's solution with or without paclitaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Taxol is an effective chemotherapeutic used to treat cancer patients; it binds to and stabilizes MT, causing abnormal MT aggregation (20). Immunofluorescent staining revealed that in the absence of Taxol, tubulin was widely distributed throughout the cytoplasm and accumulated in the perinuclear regions of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Taxol is an effective chemotherapeutic used to treat cancer patients; it binds to and stabilizes MT, causing abnormal MT aggregation (20). Immunofluorescent staining revealed that in the absence of Taxol, tubulin was widely distributed throughout the cytoplasm and accumulated in the perinuclear regions of cells.…”
Section: Resultsmentioning
confidence: 99%
“…The epineurium and perineurium are the most likely candidates for load‐bearing. In one study, peeling of the epineurium of rat sural nerves decreased nerve modulus by up to 5‐fold, with the perineurium intact . On the other hand, the perineurium—which consists of collagen, elastic fibers, and the basal lamina—has also been posited as the major load‐bearing layer of the nerve; indeed, rabbit tibial nerves lost most of their load‐bearing capabilities with perineurial breakage at strains of 27% beyond in‐situ strain .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, peeling of the epineurium of rat sural nerves decreased nerve modulus by up to 5-fold, with the perineurium intact. 37 On the other hand, the perineurium-which consists of collagen, elastic fibers, and the basal lamina 1,39 -has also been posited as the major load-bearing layer of the nerve; indeed, rabbit tibial nerves lost most of their loadbearing capabilities with perineurial breakage at strains of 27% beyond in-situ strain. 41 In both of these studies, as well as others, 3,42 the endoneurium and axons were spared under nerve tension, suggesting that axons did not sense or bear the same loads as surrounding connective tissue.…”
Section: Decoupled Regional Variability In Axonal Tortuosity Andmentioning
confidence: 99%
“…The strongest connective tissue layers in peripheral nerves are the perineurium and, to a lesser extent, the epineurium. Changes in the epineurium and perineurium extracellular matrix composition are likely to have significant effects on the biomechanical properties of acellular nerve [32]. The connective tissue from the epineurium forms a layer of fiber membrane at the 3rd day postoperatively and then forms collagen at the 8th day.…”
Section: Discussionmentioning
confidence: 99%